Improved badminton forehand smash through training methods - Sholeh, M.; Fitria Yulianto, P.; Kuncoro, B. (International Journal of Multicultural and Multireligious Understanding, 2020)
Badminton training can not only be trained at the national level and regional level training, but many Indonesian people open mass training. Training in achieving achievement cannot be separated from the right training program. So UTP Surakarta students, especially PKO study programs, are required to be able to excel in the badminton sport. This study aims to determine how much influence the plyometric training and weighted training have on the improvement of smash fore hand badminton among students in the achievement of Tunas Pembangunan Surakarta university. This research is using experimental method. The data collected in this study are quantitative data. Based on the results of the research and the results of data analysis, the following conclusions were obtained: (1). There is a difference in the effect between the effect of plyometric training and weight on the forehand smash ability with a t-value of 8.88, while the t-table at the 5% significance level is 1.72. Based on these results, it can be concluded that there is a significant difference between groups 1 and 2. (2). plyometric exercises have a better effect on improving the ability of forehand smashes. group 1 has an increase percentage of 33.7%. Meanwhile, group 2 had an increase of 30.5%.